Feasibility and safety of upper limb extremity ergometer exercise in the cardiac intensive care unit in critically ill patients with cardiac disease: a prospective observational study - Hirakawa, Kotaro; Nakayama, Atsuko; Arimitsu, Takeshi; Kon, Kazuki; Ueki, Hiromichi; Hori, Kentaro; Ishimoto, Yuki; Ogawa, Ayaka; Higuchi, Ryosuke; Hosoya, Yumiko; Nanasato, Mamoru; Isobe, Mitsuaki (Frontiers in Physiology, 2025)
BackgroundThere is no established method for early bed rehabilitation of patients after cardiogenic shock (CS) who require mechanical circulatory support (MCS). This study aimed to evaluate the safety of early upper limb extremity ergometer exercise in critically ill patients with CS or at risk for CS.MethodsThe study was conducted as a prospective, single-center feasibility and observational study. Patients with CS or at risk for CS in the cardiac intensive care unit were enrolled. Upper limb extremity ergometer exercise was performed with alternating intervals of exercise and rest, in parallel with the rehabilitation program focused on early mobilization. A multidisciplinary team was established to determine the criteria for exercise initiation and cessation. Endpoint measures included exercise-related adverse events (circulatory or respiratory failure requiring new medical intervention, inability to continue device support, bleeding requiring hemostatic treatment at the insertion site, and exercise-related skeletal pain), vital signs, and subjective symptoms.ResultsForty-seven sessions in 28 patients (71 ± 15 years, 75% male) were included in the analysis. MCS was used in 86% of the patients, and rehabilitation was initiated within 3 ± 1 day. Two patients had temporary dyspnea, and none discontinued exercise. There was a significant increase in heart rate (p < 0.05) and respiratory rate (p < 0.001) during exercise compared with pre-excercise, but not in systolic or diastolic blood pressure and oxygen saturation.ConclusionEarly upper limb extremity ergometer exercises for critically ill patients with CS or at risk for CS resulted in changes in heart rate and respiratory rate during exercise. However, no exercise-related adverse events occurred. Upper limb extremity ergometer exercise can be a new tool of physical therapy in the acute phase of patients after CS or at risk for CS.